PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. STARVI NUSA GEMILANG JAKARTA UTARA - Haniyati, Rt Nia; Wilandari, Angestika (LPPM Universitas Nusa Mandiri, 2023)
In the business world, company progress is the main thing amidst many competitors. The important role of employees as a strong foundation for the company's progress is an important point for related businesses. This research aims to determine the effect of compensation and motivation on employee performance at PT Starvi Nusa Gemilang, North Jakarta. The method used in this research is a quantitative approach. Primary data comes from companies with sample determination using saturated samples. The objects of this research are employees of PT. Starvi Nusa Gemilang, North Jakarta with a total of 33 respondents. The results of the research reveal that compensation and motivation variables have a positive and significant effect on employee performance. Apart from that, the F test results show that compensation and motivation simultaneously have a positive effect on employee performance at PT. Starvi Nusa Gemilang, North Jakarta. Through the results of the multiple linear regression equation, it is proven that compensation and motivation each have an influence on employee performance.